A novel 3-D photoluminescent cuprous chloride polymer based on bifunctional imidazolate/tetrazolate bridges. Issue 5 (16th January 2017) - Tang, Qiuling; Zhou, Jian; Almeida Paz, Filipe A.; Fu, Lianshe; Xiao, Hong; Zhou, Qi; Li, Ju
Abstract : The interconnection of rare [Cu2 Cl] + cations and multidentate 1-tetrazole-4-imidazole-benzene bridging ligands gives a novel 3-D cuprous chloride polymer with a bimodalfsc -3, 5-Cmce-2 topological type (L − ligand and Cu + ion: orange and blue). Abstract : A novel 3-D cuprous chloride polymer [CuI2Cl(μ5 -L)] n (1, HL = 1-tetrazole-4-imidazole-benzene) has been hydrothermally synthesized and structurally characterized.1 displays a 3-D network with a bimodalfsc -3, 5-Cmce-2 topological type constructed by the linkages of rare [CuI2Cl] + cations and L − ligands. The photoluminescence properties and density functional theory calculations of1 have also been studied.